FRAMING AND SENTIMENT ANALYSIS OF GERINDRA PARTY POLITICAL COMMUNICATION ON TWITTER (X) TOWARDS THE 2024 ELECTIONS - Khaq, Ilnafi Sabilal; Wulandari, Lia (JWP (Jurnal Wacana Politik), 2024)
This research investigates the strategic utilization of political communication by the Gerindra Party on the Twitter platform (X) leading up to the 2024 General Election in Indonesia. With a focus on the adoption of the ‘gemoy’ label by the public, subsequently becoming a framing tool for Prabowo, this shapes a positive image and significantly enhances his popularity. Through a comprehensive analysis of sentiment and engagement displays on social media, this study reveals the effectiveness of Gerindra’s political content in capturing public attention, signaling a paradigm shift in the dynamics of political communication in the digital era. The research adopts a quantitative methodology, employing a descriptive approach. Data collection involves direct interviews with the Public Relations Division of the Gerindra Party and utilizes netnography, combining online observations and content analysis of user interactions on Twitter (X) with the official Gerindra Party account. The results of the study demonstrate evolving emotional response dynamics over time, highlighting the adept use of framing strategies by the party. This research provides valuable insights into the transformative impact of social media on political communication, offering a deeper understanding of how political narratives are shaped and influence public opinion leading up to the general election.